A evolução da teoria da desconsideração da personalidade jurídica no direito brasileiro - Siervi Neto, Carmine de (2007)
This work aims at the study of the evolution of the theory of the disrespect of the corporate entity in the Brazilian Positive law. In the first chapter, the institute of the legal entity is defined followed by a brief explanation about the historical and terminological data. In addition, the most important existing theories regarding the legal nature of the legal entity are described and its classification and constitution are analyzed. Finally, the civil liability and corporate domicile, as well as the ways of the legal entity extinction are analyzed. In the second chapter, after the analysis of the origin of the theory of the disrespect of the corporate entity, the existing theories of the disrespect applied in Brazil and over the world are identified through the definition of its essential elements, which are, the fraud and the abuse of process, and through the principle of the patrimonial autonomy. Furthermore, a brief report concerning the Economic Analysis of the Law is presented, in order to demonstrate how the studies effected by the School of Chicago have assisted the Brazilian magistrates in the correct application of the theory of the disrespect of the corporate entity. At the end of this chapter, there is a demonstration of how important legal systems have faced the problem of the dissimulated use of the institute of the legal entity world-wide, followed by an analysis of some examples of the law, doctrine and jurisprudence. At the third and last chapter, it is demonstrated how the theory of the disrespect of the corporate entity was incorporated in the Brazilian legal system, pointing out the rightness and the mistakes made by the legislators and judges, in several legal areas (civil, consumer, environmental, tax, economic and labor law) while applying the theory of the disrespect of the corporate entity